Substance and process of creation of integrated competitive advantage - Lošťáková, Hana; Kohoutová, Martina (Univerzita Pardubice, 2002)
A competitive advantage in the global market is not a simple individual benefit for a consumer but a complex set of attributes raising of satisfaction his/her needs. However, it must be multidimensional and a company must create an "integrated product" which provides the consumer with expected parameters, and at the same time, something extra. It is necessary to create a new type of a competitive advantage - an entegrated competitive advantage. A company can built its integrated competitive advantage with a new approach of satisfying customer's needs in the following principle: to supply customers with special benefits together with the lowest selling price of a product and reducing other costs and resources of a customer. The basis for creating integrated competitive advantages must be a process of systematic strategic marketing analysis. The advantage of such an analysis lies in that it can help to create permanent active competitive advantages and facilitates getting ahead of competition.
Keywords: trh; analýza trhu; integrační procesy; soutěž; zákazníci; strategický marketing